A study of the comparative clinical profiles of scrub typhus, spotted fever group, and typhus group rickettsial infections at a rural tertiary care hospital - Vasantha Kamath; B Hima Bindu; Shreyashi Ganguly (Wolters Kluwer Medknow Publications, 2020)
Background: The rickettsioses represent a major cause of acute febrile illnesses worldwide. The greatest challenge lies in diagnosing rickettsioses in a timely manner early in the course, when antibiotic use is most effective. In most cases clinical suspicion together with a positive serology is employed to make the diagnosis of rickettsiosis. Aim and Objective: To study the syndromic differences, if any, amongst the three groups of rickettsial infections present in India. Methods: This was a cross-sectional observational study that evaluated a total of 172 cases of rickettsial fever out of a pool of 778 cases of acute febrile illness between the June 2017 and March 2019. A careful search for eschar, lymphadenopathy and rashes was made. Weil Felix test was done after exclusion of other infections like malaria, dengue, enteric fever. To avoid the possibility of false positives, a single titer dilution >1:320 was considered positive for rickettsioses. Results: Fever was seen in all cases. Myalgia (81·5%), headache (72·8%), and splenomegaly (51·9%) were common in scrub typhus. Eschar was seen in only 8·4% cases. Spotted fever group presented with fever of shorter duration of less than seven days (64·7%), and gastrointestinal symptoms like vomiting (74·5%) and diarrhea (13·7%) were predominantly seen. Spotted fever group had macular rash as predominant sign. Typhus group presented with fever of longer duration of more than fourteen days (50%) and respiratory symptoms like cough (65%). Hepatomegaly was present in 35% and lymphadenopathy in 7·5%. Conclusion: Rrickettsial infections remain a diagnostic challenge in resource-poor settings. Therefore, it is important to recognize the clinical features promptly, include rickettsioses in the differential diagnoses, and consider early initiation of appropriate treatment.